The Domination of Mother Earth, Gender-Based Violence, and the (Dis)Ease of Eve - Mary Hearns-Ayodele; Glencie Rhedrick; Burdette D. Lowe (African Journal of Gender and Religion (AJGR))
The misuse of religious texts, particularly the Genesis creation story, has historically been used to justify the exploitation of both the Earth and women. This justification, rooted in patriarchal interpretations of scripture, has led to environmental degradation and gender-based violence (GBV) and disproportionately affected marginalized communities, especially women of color. This article examines the interconnectedness of these issues, exploring how the domination of “Mother Earth” and the subjugation of women are intertwined. By analyzing the historical context, religious interpretations, and societal structures that perpetuate these forms of violence, this article aims to shed light on the urgent need for an intersectional approach to address both environmental destruction and GBV. Through a critical examination of the “(Dis)ease of Eve”, this article challenges traditional narratives and seeks to reclaim the power and agency of women, particularly women of the African Diaspora, in the fight for a more just and sustainable future.